Translating Ekphrastic Precarity - Collard, Christophe (TTR)

(untitled) (Association canadienne de traductologie, 2025)
In his first-century AD Progymnasmata, Theon defines ekphrasis as bringing “what is illustrated vividly before one’s sight.” Today, the term tends to be more narrowly associated with literary descriptions of visual art. Either way, ekphrasis foregrounds a double representation given that “what [it] represents in words must itself be ‘representational ’  ” (Heffernan, 1993; my italics). The 2021 book Le tournoiement des ombres (The Swirling of Shadows, 2024) by American visual artist Holley Chirot and Luxembourg poet/gallerist André Simoncini could prima facie be considered a classic case of ekphrasis, with its 29 poems and equal number of engravings. The images, though, depict a dreamlike, enigmatic world of hybrid creatures in constant metamorphosis: half-beasts, half-humans, and sometimes half-objects that weightlessly form or float in chimerical places. Difficult as it is to “represent” a representationality so inherently precarious, the ekphrastic logic is further problematized by Simoncini’s poetic language in which vocables bounce off one another in a swirling storm of paradoxically hyper-precise lexicality. It is an invitation for the reader to engage with a self-reflexive work, reflect on the precarity of intersemiotic interpretations, and participate in a dialogue addressing the very fundaments of signification. A Luxembourg-Italian hybrid living and working in the multilingual microcosm of Luxembourg City, André Simoncini is also a translator by training. Accordingly, his poetic experimentation partly explains his predilection for precarity and defiance of dominant discourses. Grounded in an understanding of translation as a multidisciplinary balancing act, his work encourages its translators to reassess the fundamentals of their craft. This article retraces a practice-based journey—from recognizing the book’s intrinsic complexity to tackling its stylistic and epistemological challenges— with the aim of mining the work’s heuristic potential and expanding the translator’s conceptual toolkit.